2017
DOI: 10.3389/fnbot.2017.00031
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects on the Elderly People's Motor Control by Wearable Skin-Stretch Device Combined with Haptic Joystick

Abstract: Cutaneous sensory feedback can be used to provide additional sensory cues to a person performing a motor task where vision is a dominant feedback signal. A haptic joystick has been widely used to guide a user by providing force feedback. However, the benefit of providing force feedback is still debatable due to performance dependency on factors such as the user's skill-level, task difficulty. Meanwhile, recent studies have shown the feasibility of improving a motor task performance by providing skin-stretch fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Wearable Skin-Stretch Device Combined with Haptic Joystick [31], this wearable technology is designed to facilitate the operation of the wheelchair that used by the elderly, so they do not have to rely on others to push it. This tool is very easy to operate.…”
Section: Wearable Technologymentioning
confidence: 99%
“…Wearable Skin-Stretch Device Combined with Haptic Joystick [31], this wearable technology is designed to facilitate the operation of the wheelchair that used by the elderly, so they do not have to rely on others to push it. This tool is very easy to operate.…”
Section: Wearable Technologymentioning
confidence: 99%
“…Finally, people in need of a power wheelchair often show upper limb weakness or reduced mobility, a condition that can make difficult to maneuver a kinesthetic controller. In this respect, the only non-kinesthetic solution has been presented by Yoon et al [25], where skin stretch feedback was used either alone or combined with kinesthetic feedback provided by a grounded interface. Results show that control performance significantly improved when the combined skin-stretch/kinesthetic feedback was applied.…”
Section: Introductionmentioning
confidence: 99%
“…One widely-accepted idea is that human sensorimotor systems utilize the error feedbacks for motor adaptation 29 . Several studies have reported that amplifying the movement errors could enhance the rehabilitation outcomes, which is sometimes referred to as an error augmentation 13,30,31 . Although rehabilitation may include internal sources of adaptation such as motor imagery, these are not the focus of this study.…”
Section: Introductionmentioning
confidence: 99%